Taktik Bunyi Melawan Sepi : Studi Sonic Ethnography Mengenai Perubahan Iklim Di Timbulsloko, Sayung, Demak - Fauzanafi, Muhammad Zamzam; Smith, Breezy S Putri Samudra (Universitas Padjadjaran, 2024)
This research aims to listen and understand the sonic experience of Timbulsloko people as they live in a village that is sinking caused by climate crisis and human dominated development. Using sonic ethnography as its method, this research finds that Timbulsloko people experience sepi (silent) or suwung (void) which is a constant reminder of their condition. To navigate their life against the suwung, people of Timbulsloko is actively creating a condition of rame (noisy, festive, abundance) and seneng (happy) by listening loud dangdut music and Qur’an recitation through big sound systems.